"This is NOT a #humblebrag, this is just a #brag": The pragmatics of self-praise, hashtags and politeness in Instagram posts. (April 2018) - Matley, David
Highlights: I investigate self-praise and hashtag use on Instagram. The hashtags #brag and #humblebrag place the illocution of the speech act on record. Hashtags are used to violate pragmatic norms while showing an awareness thereof. Self-praise on Instagram involves both mitigation and aggravation of face threat. Hashtag use is a key element of positive presentation of the self online. Abstract: Social media can be seen as "sites of self-presentation and identity negotiation" whose affordances facilitate the production and promotion of both individual and collective identities (Papacharissi, 2011, pp. 304–305). From a pragmatic perspective, self-promotion and self-praise are interactionally risky acts. While some studies have shed light on self-praise in online communities, little attention has been paid to the pragmatic function of the affordances of digital media such as hashtagging and multimodality in self-praising discourse. This article contributes to filling this research gap by examining the ways in which posters of "bragging" Instagram photos do face work by using the hashtags #brag and #humblebrag in interaction with positive (im-)politeness strategies. It presents the results of both a small-scale quantitative study of face work in Instagram posts labelled #fitness, #brag and #humblebrag, as well as a qualitative analysis of the mitigation and aggravation strategies used in explicitly self-praising posts. The article argues that the hashtags #brag and #humblebrag have a clear metalinguistic function as a reference to the illocution of the speech act. It also shows that they are used in a balancing act of face mitigation and aggravation strategies. Overall, the study suggests that the hashtags #brag and #humblebrag function as part of a strategy that negotiates an appropriate level of self-praise and positive self-presentation. The study adds to an understanding of the pragmatics of self-presentation on social media, and raises questions regarding the new literacies that digital media require.